Pengenalan dan Pengolahan Makanan Berbahan Daun Kelor (Moringa Oleifera) pada Anak Kelas Siswa Sekolah Dasar - Asmawati, A.; Ristiana, Evi; Pratiwi, A. Citra; Taiyeb, A. Mushawwir; Hartono, Hartono (South Sulawesi Education Development (SSED), 2023)
The community service carried out aims to provide experience for children to know Moringa-based foods. Children are given an introduction to like to consume vegetables. The community service carried out was training in making moringa fried rice using the demonstration method. A total of 12 panelists participated to assess the level of preference for Moringa fried rice which included color, taste, aroma and texture that the panelists liked. It can be concluded that the results of the dedication show that Moringa fried rice is accepted/liked by the panelists and can be used as an alternative for daily consumption of highly nutritious children.